Antiaging Activity of Peptide Identified from Fermented Trapa Japonica Fruit Extract in Human Dermal Fibroblasts - Jang, Jin Dong; Kim, Minkyung; Nam, Gun He; Kim, Young Min; Kang, Sang Moon; Lee, Kee Young; Park, Young Joon (Evidence-based Complementary and Alternative Medicine, 2020)
We have previously shown that Trapa japonica fruit extract (TJE) as well as its fermented extract (FTJ) can be potentially used to treat alopecia. In the current study, a newly synthesized peptide (PEP) was detected in an active compound isolated from FTJ. Several biological assays were conducted to verify the antiaging effects of TJE, FTJ, and PEP on the skin. We examined the effects of TJE, FTJ, and PEP on cell viability, collagen synthesis, and inhibition of mRNA expression of matrix metalloproteinases (MMPs), induced by tumor necrosis factor alpha (TNF-α), in human dermal fibroblasts (HDFs). In addition, a wound-healing assay of the human keratinocyte cell line (HaCaT) and a clinical study of antiaging activity were conducted. The findings confirmed that PEP exerted an effect on cell proliferation in a dose-dependent manner. Treatment with TJE, FTJ, and PEP increased collagen synthesis but inhibited TNF-α-induced mRNA expression of MMPs. Compared with TJE and FTJ, PEP promoted a significant level of wound recovery in HaCaT cells and also exhibited antiaging effect, as demonstrated by a clinical study. These results suggest that PEP shows potential as a skin antiaging cosmetic product.